Project Selection as a FInalist in the Digital Tranformation Category of Salto Awards 2023 - Lanitis, Andreas (My University, 2026)
The European project VRTEACHER - Virtual Reality-based Training to improvE digitAl Competences of teacHERs, which is coordinated by the Cyprus University of Technology (CUT), was selected among numerous Erasmus projects form all European Countries to be among the three finalists for the SALTO AWARDS 2023 (https://saltoawards.eu/) in the category of Digital Transformation. The VRTEACHER project (https://www.vrteacher.eu/) addressed the need for modernization and digital transformation of teacher education and the lack of practical training through immersive and experiential Virtual Reality based training experiences that reflected real-life scenarios and situations faced during a crisis. The main target groups of the VRTEACHER project were pre-service student teachers (higher education students, Ph.D. candidates, etc.), and in-service teachers. The project involved six partners, Cyprus University of Technology (Cyprus / Coordinator), University of the Aegean, University Carlos III of Madrid (Spain), Fundación Siglo22 (Spain), Future In Perspective Limited (Ireland), Commonwealth Centre for Connected Learning (Malta). The project was coordinated by the Social Computing Research Center, through the Visual Media Computing Research Laboratory of the Department of Multimedia and Graphic Arts, Cyprus University of Technology by Professor Andreas Lanitis and by post-doc researcher Dr. Kalliopi-Evangelia Stavroulia. The VRTEACHER project, funded under Key Action 2 of the Erasmus+ program (01/06/202131/05/2023, 2020-1-CY01-KA226-SCH-082707), was successfully implemented in the partner countries training more than 300 in-service and pre-service teachers.
Keywords: Sciences